2018
DOI: 10.1159/000493223
|View full text |Cite
|
Sign up to set email alerts
|

YXQ-EQ Induces Apoptosis and Inhibits Signaling Pathways Important for Metastasis in Non-Small Cell Lung Carcinoma Cells

Abstract: Background/Aims: Lung cancer is one of the most prevalent malignancies in the world. The 5-year survival rate for non-small cell lung cancer (NSCLC) patients is only approximately 15%, with metastasis as the primary cause of death. This study was aimed to investigate cytotoxic effect of external qi of Yan Xin Qigong (YXQ-EQ) toward human lung adenocarcinoma A549 cells as well as its effect on signaling pathways promoting migration, invasion and epithelial-to-mesenchymal transition (EMT) in A549 cells. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Cell viability was determined using MTS [3-(4, 5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium, inner salt] assay with a CellTiter 96 Aqueous One Solution Cell Proliferation Assay kit (Promega, Madison, WI) according to the manufacturer's instructions. (Yan et al 2018) After exposure to AgNPs (24 h and 48 h), cells were washed three times in PBS and the MTS reagent was added in HBSS buffer (20 ll and 100 ml, respectively) to wells. Cells were then incubated for 30 min at 37 C. The absorbance reading was done at 490 nm using a FLUOstar Omega plate reader (Germany).…”
Section: Viability Assay (Mts)mentioning
confidence: 99%
“…Cell viability was determined using MTS [3-(4, 5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium, inner salt] assay with a CellTiter 96 Aqueous One Solution Cell Proliferation Assay kit (Promega, Madison, WI) according to the manufacturer's instructions. (Yan et al 2018) After exposure to AgNPs (24 h and 48 h), cells were washed three times in PBS and the MTS reagent was added in HBSS buffer (20 ll and 100 ml, respectively) to wells. Cells were then incubated for 30 min at 37 C. The absorbance reading was done at 490 nm using a FLUOstar Omega plate reader (Germany).…”
Section: Viability Assay (Mts)mentioning
confidence: 99%
“…According to data compiled by the American Cancer Society, there were 234,030 estimated new LC cases and 154,050 estimated LC-associated mortalities in the USA in 2018 (3). In terms of histology, there are two types of LC: Non-small cell LC (NSCLC) and small cell LC, of which the former makes up 85% of all cases (4). NSCLC is comprised of two subtypes: Lung squamous cell carcinoma (LUSC) and lung adenocarcinoma (LUAD) (3,5).…”
Section: Introductionmentioning
confidence: 99%
“…Yan, et al [120] found that the application of Yan Xin Qigong [121] induces apoptosis and inhibits signaling pathways important for metastasis in non-small cell lung carcinoma cells. Another Yan et al study [122] found that Yan Xin Qigong induces cell death and gene expression alterations promoting apoptosis and inhibiting proliferation, migration and glucose metabolism in small-cell lung cancer cells.…”
Section: Lung Cancermentioning
confidence: 98%